Syntheses and Transformations of Sulfinamides - Zhang, Qiaoling; Xi, Jufang; Ze, He; Qingle, Zeng (Synthesis, 2021)
Sulfinamides, especially enantiopure sulfinamides, are widely used in organic and medicinal synthesis. Syntheses and transformations of racemic and enantioenriched sulfinamides have achieved great progress. Especially sulfinamides demonstrate interesting and valuable reactivity, which deserves to be pertinent. This review summarizes the latest development in the synthesis and transformation of sulfinamides and will be helpful for future related research.1 Introduction2 Synthesis of Sulfinamides2.1 Synthesis of Racemic Sulfinamides2.2 Synthesis of Enantiomerically Pure Sulfinamides2.3 Synthesis of Other Sulfinamides3 Transformations of Sulfinamides3.1 Condensation with Aldehydes and Ketones3.2 Reaction with Alkynes3.3 Reaction with Alkenes3.4 Reaction with Aryl and Alkyl Halides3.5 Reaction with Alcohols, Dibenzyl Ether, and Benzyl Mercaptan3.6 Synthesis of tert-Butyldisulfanyl-Substituted Hetarenes3.7 Synthesis of Asymmetric Sulfides3.8 Synthesis of N-Phosphino-sulfinamide Ligands3.9 Asymmetric Synthesis of γ-Amino Acids3.10 Sulfonylation of Heterocyclic Compounds4 Summary and Outlook
Keywords: sulfinamides; organic synthesis; transformation; organosulfur chemistry; chiral synthesis